Efficacy of a new video observational training method (intensive visual simulation) for motor recovery in the upper limb in subacute stroke: a feasibility and proof-of-concept study - Etienne Ojardias; Ahmed Adham; Hugo Bessaguet; Virginie Phaner; Diana Rimaud; Pascal Giraux (Medical Journals Sweden, 2024)
Objective: To demonstrate the feasibility and efficacy  of a new video-observation training method (intensive visual simulation) to improve upper limb function. Design: Small sample, randomized, evaluator-blind, monocentric study. Patients: Seventeen early subacute ischaemic stroke patients with complete hemiplegia were  randomly assigned to the therapeutic group (n = 8) or control group (CG, n = 9). Methods: Thirty sessions of intensive visual simulation combined with corrected visual feedback (therapeutic group) or uncorrected visual feedback (control group) were performed over 6 weeks on top of a standard rehabilitation programme. Main outcome measure: 400-point hand assessment test (400p-HA). Secondary outcome measures: Box and Blocks (B&B), Purdue Pegboard test, Minnesota. Results: The 400p-HA test improved significantly from T0 to 6 months for both groups, with a significant difference between groups at 3 months (MW-UT p = 0.046) and 4 months (MW-UT p = 0.046) in favour of the therapeutic group. One-phase exponential modelling of 400p-HA showed a greater plateau for the therapeutic group (F test p = 0.0021). There was also faster recovery of the ability to perform the B&B tests for the therapeutic group (log-rank test p = 0.03). Conclusion: This study demonstrated the feasibility and potential efficacy of an intensive visual simulation training programme to improve upper limb  function in subacute stroke patients. A larger study is needed to confirm these results.